La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Ideología argentina (Universidad Nacional de Quilmes), 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty--and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

L'amour sous Victoria : sexualité et classes populaires à Londres au XIXe siècle - Barret-Ducrocq, Françoise (Plon, 1989)
Keywords: 1800-1899; amour; approches et analyses; classe ouvrière; cours; discipline; discours dominant; europe; his4860; histoire; histoire de la sexualité; histoire et politique; inégalités; londres; premier cycle; périodes historiques; rapports sociaux de sexe; royaume-uni; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; époque victorienne

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Feminism and nationalism in the Third World - Jayawardena, Kumari (Zed Books, 1986)
Un texte fondateur du féminisme transnational Depuis vingt-cinq ans, Feminism and Nationalism in the Third World est une introduction essentielle à l'histoire des mouvements de femmes en Asie et au Moyen-Orient à la fin du XIXe et au début du XXe siècle. Dans cette enquête engageante et bien documentée, Kumari Jayawardena présente le féminisme tel qu'il est né dans le Tiers-Monde, émergeant des luttes spécifiques des femmes luttant contre le pouvoir colonial, pour l'éducation ou le vote, pour la sécurité, et contre la pauvreté et les inégalités.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; asie; cours; fem1000; féminisme décolonial; féminisme transnational; inégalités; nationalisme; premier cycle; périodes historiques; régions géographiques; sud global; systèmes d'oppressions; théories féministes

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

L'asservissement des femmes - Mill, John Stuart (Petite bibliothèque Payot, 1975)
Considéré comme l'un des premiers féministes masculins, le philosophe et économiste anglais John Stuart Mill s'efforça, dans sa vie privée comme dans sa vie publique, de démontrer la nécessité d'accorder aux femmes l'égalité avec les hommes, combat dont l'apogée fut la publication de ce livre en 1869. Justice, liberté, droit à l'éducation, au travail et au suffrage, L'Asservissement des femmes est une oeuvre majeure dans l'histoire du féminisme et de l'émancipation des femmes.
Keywords: 1800-1899; approches et analyses; cours; droits des femmes*; europe; fem1000; inégalités; phi4336; premier cycle; périodes historiques; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques; égalité femme*-homme

Essays on sex equality. - Mill, John S.; Mill, Harriet H.; Rossi, Alice S. (The University of Chicago Press, 1970)
Ce volume rassemble pour la première fois tous les écrits de John Stuart Mill et Harriet Taylor Mill sur l'égalité entre les sexes, dont _The Subjection of Women_ de John Stuart Mill, un classique de l'histoire du mouvement des droits des femmes depuis sa publication il y a cent ans depuis. Ce volume contient également un important essai d'interprétation d'Alice S. Rossi sur Mill et Harriet Taylor qui décrit et analyse leur longue relation personnelle et intellectuelle.
Keywords: 1800-1899; EDI; approches et analyses; cours; fem1000; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; systèmes d'oppressions; thématiques